Public debate in Russia : matters of (dis)order - Vakhtin, N. B. (Nikolaĭ Borisovich); Firsov, B. M. (Russian language and society., 2016)
An interdisciplinary study of Russian public debate past and present. Can we trace attempts taken in Russian history to overcome the inability to speak publicly? How do different social groups in modern Russia cope with situations when they have to participate in a public discussion and arrive at a compromise? What historic, sociological, linguistic, and psychological reasons underlie intolerance towards different opinions? Can this situation be changed? Bringing together an international team of leading historians, sociolinguists and sociologists in this field, this volume explores these questions from different methodological perspectives, using various sets of data and examining the different domains of private, public and official discourses. Offering detailed case studies of the past and present communicative successes and failures in various social groups, the book explores why Russian society is unable to reach a consensus through dialogue. The first book to offer a detailed exploration of the condition of public debate in Russia, this pioneering volume presents a truly interdisciplinary perspective on Russian language and society making it essential reading for advanced students and specialist in the fields of Slavic Studies, Cultural Studies, Sociolinguistics and Russian history, politics and sociology. Key Features. Presents a pioneering study of Russian public debate Offers a new approach to Russian modernisation through a multidisciplinary view on language and society Includes detailed case studies of the past and present communicative successes and failures in various social groups Brings together an established and international team of contributors from Russia, UK, Israel and France The first book to offer a detailed exploration of the condition of public debate in Russia, this pioneering volume presents a truly interdisciplinary perspective on Russian language and society. Offering detailed case studies of the past and present communicative successes and failures in various social groups, the contributors explore why Russian society is unable to reach a consensus through dialogue.